Difficult-to-treat pediatric obsessive-compulsive disorder: Feasibility and preliminary results of a randomized pilot trial of D-cycloserine-augmented behavior therapy - Farrell, L.; Waters, A.; Boschen, M.; Hattingh, Laetitia; McConnell, H.; Milliner, E.; Collings, N.; Zimmer-Gembeck, M.; Shelton, D.; Ollendick, T.; Testa, C.; Storch, E. (Wiley-Liss, Inc, 2013)
Background: This study examined the feasibility and preliminary effectiveness of d-cycloserine (DCS)–augmented cognitive behavioral therapy (CBT) for children and adolescents with difficult-to-treat Obsessive Compulsive Disorder, in a double-blind randomized controlled pilot trial (RCT).Methods: Seventeen children and adolescents (aged 8–18 years) with a primary diagnosis of OCD, which was deemed difficult-to-treat, were randomly assigned to either nine sessions of CBT including five sessions of DCS-augmented exposure and response prevention (ERP) [ERP + DCS] or nine sessions of CBT including five sessions of placebo-augmented ERP [ERP + PBO]. Weight-dependent DCS or placebo doses (25 or 50 mg) were taken 1 hour before ERP sessions.Results: At post treatment, both groups showed significant improvements with 94% of the entire sample classified as responders. However, a greater improvement in the ERP + DCS relative to the ERP + PBO condition was observed at 1-month follow-up on clinician-rated obsessional severity and diagnostic severity, and parent ratings of OCD severity. There were no changes across time or condition from 1- to 3-month follow-up.Conclusions: In this preliminary study, DCS-augmented ERP produced significant improvements in OCD severity from posttreatment to 1-month follow-up, relative to a placebo control condition, in severe and difficult-to-treat pediatric OCD. The significant effect on obsessional severity suggests that DCS augmentation might be associated with enhanced modification of obsessional thoughts during ERP, and warrants further investigation.